Palliative and Supportive Care Prescribing Considerations Around QT Prolongation Risk in the Context of COVID-19 (Coronavirus Disease 2019) Management. (4th September 2020) - Wong, Aaron; Keith, Claire; Gregory, Heidi; Liew, David
Abstract: COVID-19 brings with it unprecedented challenges in clinical management. An important component of care is the provision of safe and effective symptom control. Given the emerging literature reporting on the risk of QT prolongation and arrhythmias associated with COVID-19 disease and experimental therapies, we highlight some considerations for the prescribing of palliative care medications in this context. Based on the experience gained from palliative care referrals at our institution prior to and during the COVID-19 pandemic, and in collaboration with our clinical pharmacology colleagues, we outline some general prescribing principles which may assist with weighing the risks and benefits of prescribing symptomatic medications in and beyond the current pandemic.